1963
DOI: 10.1530/acta.0.0420552
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Blood Volume Following Hypophysectomy in Man

Abstract: Using 51Cr-labelled red cells, studies on the blood volume were performed before and after hypophysectomy in five patients (three cases of metastatic mammary carcinoma and two cases of acromegaly). In addition, studies were performed only after hypophysectomy in nine patients (two cases of metastatic mammary carcinoma and seven diabetic subjects). All patients were on replacement therapy with cortisone (17,21-dihydroxy-pregn-4-ene-3,11,20-trione) postoperatively, and several cases also received thyroid and sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1965
1965
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Arterial blood pressure in the supine position remains unchanged (1,3,12). Blood volume is reduced (13). Vasoconstriction is known to take place following hypophysectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Arterial blood pressure in the supine position remains unchanged (1,3,12). Blood volume is reduced (13). Vasoconstriction is known to take place following hypophysectomy.…”
Section: Methodsmentioning
confidence: 99%
“…In animals-and man hypophysectomy induces a decrease in oxygen consumption (7,8). Therefore it was concluded that G H influences erythropoiesis by increasing the oxygen need of the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…pendent samples and the Wilcoxon sign-rank test for correlated data) or the one-tailed t-test were carried out (5). Investigations in animals and man (3,4,7,8,11,13,15,16,23,24,28,31,36) produced convincing evidence justifying a one-tailed test (6,29). Since results of enzyme activity assays were not available in every patient, sample size of data was different.…”
Section: Materials a N D Methodsmentioning
confidence: 99%
See 2 more Smart Citations